Pengaturan Dan Penerapan Mitigasi Risiko Dalam Penyelenggaraan Peer To Peer Lending Guna Mencegah Pinjaman Bermasalah - Inda Rahadiyan; M. Hawin (Jurnal Hukum IUS QUIA IUSTUM, 2020)
Public interest in financial technology in the form of peer-to-peer lending (P2PL) is growing rapidly as an alternative provider of loans. In addition, it is a promising investment platform. The process of lending and borrowing between the lender and the recipient of the loan takes place through a system provided and managed by the organizing company that it provides various conveniences. However, the implementation of P2PL is also inseparable from the occurrence of non-performing loans. Regulating and implementing the risk mitigation of non-performing loans is an important issue in the implementation of P2PL. So far, there is no specific regulation regarding risk mitigation of P2PL implementation for non-performing loans, which results in weak legal certainty and protection for lenders. Therefore, the problems examined in this study include: First, how is the risk mitigation arrangement for non-performing loans in the implementation of P2PL in Indonesia? Second, how is the implementation of risk mitigation by the companies that carry out P2PL as an effort to prevent non-performing loans? This research is a normative legal research with a statutory and a conceptual approach. The results of the study concluded that: first, the P2PL risk mitigation arrangements, especially the risk of non-performing loans in Indonesia, are still scattered in several Financial Services Authority regulations and Bank Indonesia regulations. Second, the organizing company implements non-performing loan risk mitigation based on their respective internal policies.